GURU SEBAGAI ARSITEK KARAKTER: KORELASI KOMPETENSI KEPRIBADIAN DAN KESUKSESAN BELAJAR DALAM PENDIDIKAN AGAMA KRISTEN - Yuel Sumarno; Sadrakh Sugiono; Agusti Layung (Bethel Press, 2023)
This study aims to explore the role of Christian Religious Education (PAK) teachers as character architects through their personal competence and its impact on students’ learning success. The research employed a constructive qualitative approach, collecting data through classroom observations, field notes, and document analysis, including lesson plans, students’ development records, and academic results. Data were analyzed using Miles and Huberman’s interactive model, comprising data reduction, display, and conclusion drawing/verification. Findings reveal that PAK teachers with well-developed personal competence, characterized by emotional stability, integrity, exemplary conduct, and the ability to build positive relationships, were able to create a safe and inclusive learning climate. Such conditions fostered students’ motivation, discipline, and active engagement in learning. Moreover, PAK teachers who served as role models played a vital role in shaping students’ Christian character, evident in their attitudes of respect, responsibility, and honesty. These positive influences also contributed to improved academic achievement.The study highlights that the success of Christian Religious Education depends not only on teachers’ mastery of subject content and pedagogical strategies but also on their personal character. Therefore, strengthening teachers’ personal competence should be an integral component of professional development in Christian education.